Uncertainty in the planning phase of public projects: Its scope, consequences, and possible remedies - Dorota Kuchta; Paolo Canonico; Vincenza Capone; Guido Capaldo (Administrative Sciences, 2023)
The aim of the study was to assess the uncertainty scope and types present in public projects, with uncertainty defined as a lack of knowledge, and to formulate recommendations for improving the success rate of public projects. Apart from a literature review, a questionnaire was administered among 60 Italian and 40 Polish public-project managers. Questions about the level of knowledge of various project aspects (e.g., project stakeholders or project environment) in the project-planning phase were asked. It was found that, in their own opinion, knowledge of essential aspects of public projects in the planning stage was fairly low among public-project managers. On top of that, the results showed in which areas, and in which of the two countries, the uncertainty was mostly present. This type of research has not been identified in the literature. In both countries, an especially high uncertainty level characterized project stakeholders. The survey's conclusions are juxtaposed with results from the literature: the negative influence of lack of knowledge (i.e., uncertainty) on project success, specific features of public projects and public-project managers, and the fact that certain negative phenomena influencing project success are significantly more present in the public than in the private sector. Our results indicate which aspects of public projects in both countries should be subject to deep changes-as far as information collecting and processing, in the project-defining and planning phase, is concerned. All this leads to recommendations of measures to be introduced in the public sector with respect to public-project management, e.g., the establishment of project management offices, project knowledge sharing, project management training-all focused on the identified uncertainty types in public projects, such as management of project stakeholders. The main limitations of the study were the relatively small sample sizes, a non-random sample selection, a bias due to misinterpretation of the questions, and cultural differences.
Keywords: 350; public project; public-project manager; public-project planning; uncertainty in projects